The two sides of CEO option grants at the IPO - Chahine, Salim; Goergen, Marc (Journal of Corporate Finance, 2011)
This paper examines the impact of CEO IPO option grants on IPO underpricing. Contrary to Lowry and Murphy (2007) who do not find a relationship between the two, this paper finds such a relationship when board independence, the power of the CEO and venture capitalists (VCs) are taken into account. The results are threefold. First, powerful CEOs are able to reap substantial gains from IPO options, to the detriment of the shareholders. Second, young, powerful VCs use IPO option grants to bribe the CEO to agree to an early IPO which will leave more of the existing shareholders' money on the table. Finally, IPO options only work as a value-enhancing incentive in the presence of strong boards.